The Political Economy of Budget Deficits - Alesina, Alberto; Perotti, Roberto (Washington, D.C. : International Monetary Fund, 1994)
This paper provides a critical survey of the literature on politico-institutional determinants of the government budget. We organize our discussion around two questions: Why did certain OECD countries, but not others, accumulate large public debts? Why did these fiscal imbalances appear in the last 20 years rather than before? We begin by discussing the 'tax smoothing' model and conclude that this approach alone cannot provide complete answers to these questions. We will then proceed to a discussion of political economy models, which we organize in six groups: (i) models based upon opportunistic policymakers and naive voters with 'fiscal illusion;' (ii) models of intergenerational redistributions; (iii) models of debt as a strategic variable, linking the current government with the next one; (iv) models of coalition governments; (v) models of geographically dispersed interests; and (vi) models emphasizing the effects of budgetary institutions. We conclude by briefly discussing policy implications.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet